Molecular Ultrasound Imaging of the Spinal Cord for the Detection of Acute Inflammation. (November 2017) - Volz, Kevin R.; Evans, Kevin D.; Kanner, Christopher D.; Buford, John A.; Freimer, Miriam; Sommerich, Carolyn M.
Molecular ultrasound imaging provides the ability to detect physiologic processes non-invasively by targeting a wide variety of biological markers in vivo. The current study investigates the novel application of molecular ultrasound imaging for the detection of neural inflammation. Using a murine model with acutely injured spinal cords (n=31), subjects were divided into four groups, each being administered ultrasound contrast microbubbles bearing antibodies against various known inflammatory molecules (P-selectin, vascular cell adhesion protein 1 [VCAM-1], intercellular adhesion molecule 1 [ICAM-1], and isotype control) during molecular ultrasound imaging. Upon administration of the targeted contrast agent, ultrasound imaging of the injured spinal cord was performed at 40MHz for seven minutes, followed by a bursting pulse. We observed significantly enhanced signals from contrast targeted to P-selectin and VCAM-1, using a variety of outcome measures. These findings provide preclinical evidence that molecular ultrasound imaging could be a useful tool in the detection of neural inflammation.